Polemic on the Repatriation of Indonesian Citizens Involved in Terrorism in Syria - Sukma Adelia; Nabila Tri Ananda; Siti Annisa (Lembaga Studi Agama dan Masyarakat Aceh, 2025)
The repatriation of Indonesian citizens (WNI) involved in terrorism in Syria has become a complex debate in the realm of national and international policy. This issue involves aspects of national security, human rights, and efforts to deradicalize and social reintegrate. This study aims to analyze the factors that influence the policy of repatriating ex-combatant Indonesian citizens, including legal, political, and socio-cultural considerations. The method used is a qualitative approach with literature studies and relevant policy analysis. The results of the study indicate that the government is faced with a dilemma between maintaining national security stability and fulfilling the obligation to protect its citizens. In addition, the challenges in implementing deradicalization and reintegration programs are crucial factors that need to be considered. This study recommends synergy between state institutions, civil society, and international organizations in handling the repatriation of ex-combatant Indonesian citizens comprehensively.